Management of Class II Division 1 Subdivision malocclusion using unilateral bicuspid extractions and fixed functional appliance: A Two Year Follow-Up - Kohli, Sarvraj; Kohli, Virinder; Kochhar, Gagan Deep (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2021)
Introduction:  Management of Class II Subdivision cases pose a clinical dilemma and require a careful diagnosis to ascertain the source of asymmetry. Various treatment modalities involving: different protocols of tooth extractions; molar distalization; fixed functional appliances or orthognathic surgery have been proposed for the same.Objective:       This article reports a unique approach for management of a severe skeletal Class II with Angle’s Class II Division 1 subdivision malocclusion using unilateral bicuspid extractions in mandibular and maxillary arches  and a fixed functional appliance.Results:         A 13 year 1 month old male in CVMI transition stage was successfully treated. Extraction of #44 was done to alleviate crowding in the mandibular anterior region and #15 was extracted to protract #16 to achieve a Class II molar relationship. A pre-functional Class II molar and canine relationship with co-incident midlines was achieved. The functional phase consisted of a fixed functional appliance (Forsus FRD) for mandibular advancement to correct the severe skeletal Class II. Class I molar and canine relationships were achieved with reduction of facial convexity and overjet. Result remained stable 24 months after treatment. The improvement can be quantified by the reduction in scores of orthodontic indices measured pre and post treatment.Conclusions:                        Management of Class II subdivision malocclusion requires careful planning. This paper presents a unique approach utilizing unilateral extractions and fixed functional appliance to address severe skeletal Class II discrepancy and the subdivision dilemma.
Keywords: Class II malocclusions; Unilateral extractions; Forsus FRD; Fixed Functional Appliances; Class II subdivision management.